How Immigrants Impact Their Homelands - Najam, Adil; Eckstein, Susan, 1942- (Book collections on Project MUSE., 2013)
This collection examines the economic, social, and cultural effects that immigrants have had on their home countries, including China, Cuba, India, Mexico, Mozambique, the Philippines, and Turkey.